Perfil clínico, genético e nutricional de pacientes com fibrose cística em Sergipe - Meneses, Daniela Gois (2024)
Cystic Fibrosis (CF) is a disease with high phenotypic variability in mixed populations. Knowing its various forms of presentation and genotypes contributes to early clinical diagnosis and to clinical management. The success of the treatment depends on a good nutritional status, which contributes to better lung function and longer survival of CF patients. The objective of this study was to describe the clinical, genetic and nutritional profile of CF patients in Sergipe, Brazil, in two independent stages. Both stages consisted of a cross-sectional study. Clinical data were extracted from medical records. In the first stage, the clinical, laboratory, and genotypic characteristics of patients diagnosed between 2007 and 2021 were described. Fifty-eight (58) patients were included in the study and 53.5% were diagnosed through clinical suspicion. The median age at diagnosis was 4.7 months (IQR: 1.5–14.8 months). Five patients had false- negative results in the newborn screening. Faltering growth was the most frequent clinical manifestation. Bronchiectasis and a history of pneumonia predominated in patients > 10 years of age, and wasting, underweight, and electrolyte imbalances were more frequent in children < 2 years old. Sequencing of the CFTR gene identified 27 genotypes, with at least one class I–III variant in all patients, and nine variants that are rare, previously undescribed, or have uncertain significance (619delA, T12991, K162Q, 3195del6, 1678del>T, 124del123bp, 3121-3113A>T). The most frequent alleles were p.Phe508del, p.Gly542*, p.Arg334Trp, and p.Ser549Arg. The second stage was carried out from 2021 to 2023. To describe the anthropometric status and nutritional biomarkers of CF patients who are consuming conventional fat-soluble vitamins and to examined the impact of socioeconomic status and adherence to treatment protocols on the evaluated nutritional parameters. Weight-for-age (WAZ), height-for-age (HAZ), and BMI-for- age (BAZ) indices, and serum concentrations of vitamins A, D, E, B12, folic acid, and markers of iron status were evaluated in CF patients diagnosed with exocrine pancreatic insufficiency taking fat-soluble vitamins in conventional formulations. A multivariate analysis was performed to identify the principal factors influencing the nutritional parameters. 40 patients <16 years old were included in this study. The median age was 6.75 (IQR: 2.85–11.61), 45% belonged to a low socioeconomic class, and 70% reported adherence to their treatment regimen. Wasting was detected in 17.5% of the patients. Vitamins A, D, and E were deficient in 2%, 5%, and 5% of the study population, respectively. Non-adherence to treatment was the main variable influencing the serum levels of the fat-soluble vitamins assessed. It was concluded that malnutrition and electrolyte imbalances were the most frequent phenotypes for children < 2 years and were associated with genotypes including 2 class I–III variants. Rare and previously undescribed variants were identified. The p.Gly542*, p.Arg334Trp, and p.Ser549Arg alleles were g the most frequent variants in this population. The prevalence of deficiencies in vitamins A, D, and E among the participants was relatively low, notwithstanding the challenges posed by exocrine pancreatic insufficiency and despite the provision of these vitamins in conventional formulations. The critical determinant for the serum levels of these vitamins was the adherence to the supplementation protocol.